English Phonemic Awareness of Students with Visual Disabilities - Arum, Aghnessia Kusumaning; Lintangsari, Alies Poetri; Perdhani, Widya Caterine (Indonesian Journal of Disability Studies, 2021)
Most of researches have reported the significance of English phonemic awareness to the success of learning English, but less discussions involving students with visual disabilities. Students with visual disabilities lacks of visual input and form a strong sensitivity to audio input, researches have reported that this condition affect their spelling ability, yet, their ability in recognizing English phonemes has been less explored especially in Indonesia. Thus, this research aims to describe the phonemic awareness of students with visual disabilities who learn English as Foreign Language. The participants of this research are students with visual disabilities whether active or passive braille user. 7 students with visual disabilities participated in an Online English Phonemic Awareness Test. Two independent raters rated the data independently. Interrater agreement was applied to ensure the objectivity of two independent interrater. The findings show that students with visual disabilities are aware of consonants Fricative alveolar, Plosive bilabial, and Plosive alveolar sounds but struggling with Fricative velar and Affricative velar sound, they are also aware of vowels Close mid front vowel, Close front long vowel sounds, Close mid back vowel and Open central vowel but struggling in identifying Open back vowel, Close mid central vowel, and Open mid back vowel. English phonemic awareness is a very important basic thing in language learning. However, it will be very challenging for ESL learners, especially those who learn are blind students because of certain obstacles that blind students have so that strategies are needed in language learning.